Pemberdayaan Perempuan melalui Pelaksanaan Continuity of Care dalam Pelayanan Kebidanan - Yulizawati Yulizawati; Lusiana El Sinta B; Rafika Oktova; Erda Mutiara Halida; Ulfa Farrah Lisa; Laila Rahmi; Aldina Ayunda Insani; Uliy Iffah; Miranie Safaringga; Feni Andriani; Fitrayeni Fitrayeni; Henni Fitria; Feri Anita Wijayanti; Hindun Mila; Rahmayani Afrah; Marzatia Yulika (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
The Maternal Mortality Rate (MMR), which is still high and far from the Sustainable Development Goals (SDGs) target, encourages midwives to increase promotive and preventive efforts in providing midwifery care and reproductive health. One of the efforts of midwives is to provide midwifery care based on Continuity of Care (CoC). Midwifery care covers the entire life cycle, from preconception, pregnancy, childbirth, postpartum, newborns, neonates, toddlers, adolescent preschoolers, and childbearing ages to the elderly. This sustainable care is expected to be able to explore the problems that exist in individuals and to overcome these problems by empowering husbands, families and communities. This activity aims to increase the number of better health degrees for women of childbearing age in every phase they go through, physically and psychologically/mentally, in the era of the Covid-19 pandemic. The method was carried out by interviewing groups of women in the preconception period, groups of pregnant women, postpartum mothers, mothers who have babies and toddlers, and women of childbearing age. It involved Independent Practice Midwives in the Cities of Padang, Padang Panjang and Pariaman by providing communication, information, education, and counselling. Each group has increased knowledge of physical and psychological needs in every phase of their life and sufficient involvement of husband or family in pregnancy, postpartum and newborn phases. It is necessary to increase community empowerment in every phase to achieve health status in every cycle of a woman's life.